Motivasi Petani Menjadi Anggota Kelompok Tani Cahaya Pelita di Desa Liningaan Kecamatan Maesaan Kabupaten Minahasa Selatan (Motivation of Farmers to Become Members of the Cahaya Pelita Farmer Group in Liningaan Village, South Minahasa Rengency) - Olivia Brenda Koleangan; Grace A. J. Rumagit; Yolanda P. I. Rori (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to describe the motivation of farmers to become members of the Cahaya Pelita farmer group in Liningaan Village, Maesaan Sub District, South Minahasa Regency. This research was conducted from February to April 2022 starting from preparation, data collection, until the preparation of research reports. The data used in this research are primary and secondary data obtained from 1 farmer group consisting of 10 members/respondents of farmer groups. The research results of showed that the motivation of farmers to become members of farmer groups is at an index value of 72% in the medium category, meaning that farmers quite agree to become members of farmer groups based on intrinsic motivation (motivation within the farmer) and extrinsic motivation (motivation from outside the farmer). With extrinsic motivation getting a percentage of 81% which is in the high category and intrinsic motivation getting a percentage of 66% which is in the medium category.